In silico study of bioactive compounds in blue shark (Prionace glauca) cartilage and its extract as anti-inflammatory agents: Studi in silico senyawa bioaktif tulang rawan hiu biru (Prionace glauca) dan ekstraknya sebagai agen antiinflamasi - Agustin, Titiek Indhira; Nursyam, Happy; Firdaus, Muhamad; Rifa’i, Muhaimin; Sare, Maria Dolorosa; Praditapuspa, Ersanda Nurma (Jurnal Pengolahan Hasil Perikanan Indonesia, 2026)
Blue shark (Prionace glauca) cartilage contains various bioactive compounds that may be beneficial to human health. This study aimed to identify bioactive compounds in shark cartilage and evaluate their potential as anti-inflammatory agents by targeting NF-kB p65 and TNF-α convertase. Shark cartilage powder and its extract were analyzed using Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS), while ligand-protein interactions were evaluated in silico via molecular docking using Autodock on the NF-kB p65 (PDB ID: 2RAM) and TNF-α convertase (PDB ID: 3EWJ) targets. LC-HRMS analysis identified 64 bioactive compounds in the cartilage powder and 141 in the extract. A total of 20 powdered compounds (powder) and 37 compounds (extract) showed mzCloud Best Match values >80%. Thirteen compounds were successfully identified, including betaine, creatine, hypoxanthine, L-norleucine, choline, caprolactam, nicotinamide, L-phenylalanine, creatinine, guanine, trigonelline, trans-3-indoleacrylic acid, and D-(+)-proline, with isocytosine and lactamide specific to the powder, and 3,5-di-tert-butyl-4-hydroxybenzaldehyde, TEMPO, and piperine specific to the extract. Docking results indicated that l-phenylalanine and trans-3-indoleacrylic acid possess high binding affinities and stably interact with the active sites of NF-kB p65 and TNF-α convertase, potentially inhibiting the pro-inflammatory pathways mediated by these two proteins. These findings indicate that shark cartilage powder and its extract show promise as candidates for anti-inflammatory therapeutic agents with low toxicity potential, which requires further validation in vitro and in vivo studies.